Responsibility in Pharmaceutical Practice: Aplication of Beyond Use Date for Compounded Preparations - Azzahra, Pratika; Genatrika , Erza (Pt. Anagata Sembagi Education, 2025)
BUD (beyond use date) is very important to maintain the quality, safety, and effectiveness of the drug after the package is opened or blended. The purpose of this study is to evaluate the implementation of BUD (beyond use date) in various pharmaceutical facilities. This study uses the Systematic Literature Review (SLR) method. This study uses a database from scopus. There are three stages carried out in mapping evaluated the application of BUD (beyond use date) in various pharmaceutical facilities, namely : 1) harvesting data, 2) data screening, 3) data analysis and visualization. From the results of data harvesting, 8 articles were published. Based on research with the SLR method that has been carried out, it can be concluded that penerapan Beyond Use Date (BUD) In pharmaceutical preparations, it is a critical aspect that affects the stability, effectiveness, and safety of the drug for patients. Previous studies have shown that adherence to medical standards has a significant impact on the success of therapy. Therefore, this study emphasizes the need for better standardization, increased pharmacist compliance, as well as further research on the impact of the implementation of BUD in clinical pharmacy. The implications of this study are addressed to the researchers and the pharmaceutical practice.